ANTI-CHIKUNGUNYA ACTIVITY OF GREEN SYNTHESIZED SILVER NANOPARTICLES USING CARICA PAPAYA LEAVES IN ANIMAL CELL CULTURE MODEL: Anti-chikungunya activity of AgNPs by using Carica papaya leaves - SULOCHANA KAUSHIK; VIKRANT SHARMA; SUNIL CHHIKARA; JAYA PARKASH YADAV; SAMANDER KAUSHIK (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of the present study is to synthesized silver nanoparticles (AgNPs) of Carica papaya L. leaves and evaluation of their anti- Chikungunya activity in vitro. Methods: The AgNPs were prepared using C. papaya leaves extract in 1:4 ratio. Synthesized AgNPs were characterized using ultraviolet-visible spectroscopy, Fourier-transform infrared spectroscopy, and scanning electron microscopy. The cytotoxicity of plant NP and 50% tissue culture infective dose of Chikungunya virus (CHIKV) were determined before antiviral assay by the 3-(4, 5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide. After that, the maximum non-toxic dose (MNTD) and ½MNTD were calculated. The absorbance values were detected using a microplate reader at 595 nm. Median tissue culture infective dose (TCID50) dose was calculated using the Reed and Muench method. In vitro antiviral activity was performed to CHIKV using NP MNTD, ½MNTD, and calculated TCID50 dose of CHIKV. Results: The MNTD and ½MNTD of C. papaya AgNPs were found to be 125 and 62.5 μg/ml, respectively. The MNTD and ½MNTD brought about 39% and 52% of CHIKV inhibition, respectively, when compared to virus control. The infected cell viability increased (14%) when treated with plant AgNPs at ½MNTD. Conclusion: There are no antiviral agents available to treat CHIKV. The medicinal plants and their metabolites are the most important source for the invention and development of new drugs against many types of disease. In view of the rapid expansion of CHIKV at the global level, there is an urgent need to develop newer anti-Chikungunya drugs with unique drugs target.